Stress Management Competency Framework in English policing. (27th November 2019) - Houdmont, J; Jachens, L; Randall, R; Colwell, J; Gardner, S
Abstract: Background: The UK Health and Safety Executive's Stress Management Competency Framework and associated questionnaire, the Stress Management Competency Indicator Tool (SMCIT), address line managers' behaviours across four competency areas. The application in policing remains unexplored. Aims: This study profiled English police officers' perception of their line managers' competencies in the framework areas. The odds of experiencing poor mental wellbeing and work attitudes associated with having a line manager with a development need on each competency area were tested. Methods: Two hundred and sixty-three police officers completed a survey comprising the SMCIT and measures of psychological distress, resilience and work engagement. Bivariate correlations were calculated to identify patterns of relationships between variables. Binary logistic regression analyses tested the odds of psychological distress caseness, low resilience and low work engagement being associated with officers' perception of their line manager having a development need on the SMCIT criteria. Results: Approximately half the participants reported their line manager had a development need on the 'Managing and Communicating Existing and Future Work', 'Managing the Individual Within the Team' and 'Reasoning and Managing Difficult Situations' competencies, and one quarter on the 'Respectful and Responsible: Managing Emotions and Having Integrity' competency. Officers' rating of their line manager having a development need on the four competency areas was associated with up to four-fold elevated odds of each undesirable state. Conclusions: The framework competency areas are relevant to English policing and offer a basis for stress reduction interventions targeted at line managers' behaviours.